The Development Of Fluxgate Magnetometer For Non-Destructive Measurement - Chew, Soon Leong; Shah Ahmad, Rashdi; Jaafar, Rosly (Penerbit UTM Press, 2001)
Non-Destructive measurements of ferromagnetic material and low frequency magnetic flux disturbance require a highly sensitive and stable magnetic sensor with directional capabilities. A magnetometer based on fluxgate princi ple that meets the requirement had been developed using a ferrite ring core. The ferrite ring core is excited by an excitation current source to achieve hysteresis condition. The pick up coil that is wound across the ring core will pick up the magnetic flux generated in the ring core. This sensing method is based on the conventional type of fluxgate magnetometer with detection of second harmonics by a phase sensitive detector. Major advantages of the fluxgate magnetometer are low cost, directional, easy to construct, reliable and rugged.